PHARMACOLOGICAL EVALUATION OF Silybum marianum (L.) SEED EXTRACT: ANALGESIC, ANTI-INFLAMMATORY, DIURETIC, AND ANTIDIARRHEAL ACTIVITIES (Journal of Medical & Health Sciences Review, 2025)
Silybum marianum (milk thistle) seeds contain a flavonoid-rich extract that has been used for liver disorders. However, it has not been extensively studied for its analgesic, anti-inflammatory, diuretic, and antidiarrheal properties. We tested an ethanolic seed extract (SME) in standard rodent models. Swiss albino mice and Wistar rats (n=8) were divided into three groups: control, standard drug, and SME-treated (100, 200, 400 mg/kg p.o.). Sample sizes were determined using power analysis (α=0.05, β=0.2) based on preliminary variability. The study evaluated analgesic activity through acetic acid writhing (visceral pain) and tail-flick (thermal nociception), as well asanti-inflammatory activity through carrageenan-induced paw edema, diuretic activity through 24-hour urine output and electrolyte excretion (versus furosemide), and antidiarrheal activity through castor oil-induced diarrhea (versus loperamide). The extract significantly reduced writhing counts (73% inhibition at 400 mg/kg, p